Clinical Evaluation on Digestive and Metabolic Parameters of a Prodosomed Enzyme Formulation, N-SORB: A Randomized, Double-Blind, Placebo-Controlled Study. (29th May 2020) - Bagchi, Debasis; Nair, Sreejayan; Smith, Derek; Nair, Rama; Downs, Berrnard; Kushner, Steve; Bagchi, Manashi
Abstract: Objectives: Optimal nutrition and natural digestive enzymes play a critical role in enhancing healthy digestion. N-SORB, a novel KD120 liquid multienzyme complex was developed and encapsulated using a SK713 SLP absorption technology (Prodosome ® ). A randomized, double-blind placebo-controlled investigation over a period of 90 consecutive days was conducted to determine the safety and efficacy of N-SORB on diverse parameters of the blood, immune health and physical health. Methods: Forty-six (age: 25.8 ± 12.1 years) healthy volunteers received either N-SORB or placebo for 90 consecutive days. Complete blood count, as well as blood glucose, liver enzymes, and lipid profile were assessed pre- and post-intervention. Serum cytokine levels were determined using ELISA. Whole Body composition analysis was performed by DEXA to determine body fat mass, lean mass and android and gynoid fat. Body weight, blood pressure, and physical health were assessed. Changes in quality of life (QOL) were examined using WHOQOL-BREF questionnaire. Sleep quality was assessed using Pittsburgh Sleep Quality Index (PSQI) questionnaire. Adverse events were monitored. This clinical investigation was followed by three case studies. Results: 40 subjects completed the study. Compared to placebo, changes in blood cell counts including hematocrit, hemoglobin, mean corpuscular volume, platelets and lymphocytes provide evidence indicating consistent trends of improvement. QOL parameters showed significant improvement in N-SORB group. A significant increase was observed in AST level in the placebo group, while, no increase was observed in the N-SORB group. In either group, no significant changes in BUN, serum creatinine, ALP, ALT, and lipid profile were observed. No adverse effects were reported. Case study volunteers also reported encouraging results. Conclusions: N-SORB exhibited trends of improvement in some RBC and immune parameters and found improvements in QOL and PSQI; but didn't significantly alter cardiometabolic parameters, lipid profile or body composition. N-SORB induced significant improvement in digestive health, metabolism and sleep pattern. Case studies indicated significant improvement in digestion, sleep pattern and metabolic health. Funding Sources: This Project was funded by VNI Inc, Lederach, PA.